The Hallyu Ef ect: Persebaran Budaya Pop Hallyu sebagai Ancaman terhadap Juche - Francis Lydia Irene Sitompul; Satwika Paramasatya (Journal of International Relations Diponegoro, 2020)
Hallyu is a phenomenon from South Korea in the form of pop-culture that spreads to various parts of the world through globalization. Cultural globalization has facilitated access to information which is going to af ect how an individual acts. The global popularity of hallyu has succeeded in building a positive image of South Korea, and also contributes to the economic growth of the country. Hallyu contains many values of freedom and democracy which are adopted by South Korea. Hallyu is very well-received by the international community, including North Korea. Juche is an ideology from North Korea that has the goal of achieving socialist revolution through three main points, namely chaju (independence), charip (self-sustenance), chawi (self-defense). The spread of hallyu whose values are contrary to juche has influenced the way of life, the trends that occur in North Korean society, and also changed the people’s perspectives on the government. It eventually af ected the people’s decision to leave their country and in South Korea. This research will use the concept of cultural globalization to analyze how hallyu entered North Korea and found that hallyu does threaten juche by the shifting behavior in North Korean society and how the government responded to the spread of hallyu in North Korea.